Ten years of hardware Trojans: a survey from the attacker's perspective. Issue 6 (30th September 2020) - Xue, Mingfu; Gu, Chongyan; Liu, Weiqiang; Yu, Shichao; O'Neill, Máire
Abstract : Hardware Trojan detection techniques have been studied extensively. However, to develop reliable and effective defenses, it is important to figure out how hardware Trojans are implemented in practical scenarios. The authors attempt to make a review of the hardware Trojan design and implementations in the last decade and also provide an outlook. Unlike all previous surveys that discuss Trojans from the defender's perspective, for the first time, the authors study the Trojans from the attacker's perspective, focusing on the attacker's methods, capabilities, and challenges when the attacker designs and implements a hardware Trojan. First, the authors present adversarial models in terms of the adversary's methods, adversary's capabilities, and adversary's challenges in seven practical hardware Trojan implementation scenarios: in‐house design team attacks, third‐party intellectual property vendor attacks, computer‐aided design tools attacks, fabrication stage attacks, testing stage attacks, distribution stage attacks, and field‐programmable gate array Trojan attacks. Second, the authors analyse the hardware Trojan implementation methods under each adversarial model in terms of seven aspects/metrics: hardware Trojan attack scenarios, the attacker's motivation, feasibility, detectability (anti‐detection capability), protection and prevention suggestions for the designer, overhead analysis, and case studies of Trojan implementations. Finally, future directions on hardware Trojan attacks and defenses are also discussed.